The management of SMEs’ human capital from the perspective of SECI model: a case study in the Multimedia Super Corridor (MSC) status companies in Malaysia / Norzanah Mat Nor, Anizah Zainuddin and Norlida Kamaluddin - Mat Nor, Norzanah; Zainuddin, Anizah; Kamaluddin, Norlida (Faculty of Business Management, 2008)
With the commencement of the Ninth Malaysian Five-year Plan (9MP) in 2007, Malaysia now has thirteen (13) years in which to achieve Vision 2020. The next questions to address are as follows: - “Is Malaysia on the right track to become a developed nation by the end of the next decade? Are Malaysians really ready for this, and what will happen in the years ahead?” The National Vision Policy (NVP) and Ninth Malaysian Plan (9MP) are entrusted to build on the success of its predecessor and set the pace for the country to be fully developed by the year 2020. In this regard, the Multimedia Super Corridor (MSC) status companies consisting mostly the small and medium enterprise (SMEs) are now considered as the growth engine for making the Sixth Challenge of Vision 2020 into a reality. Here, their knowledge workers and/or human capital have been highlighted as the most important asset for these companies. Thus, this paper provides an understanding of how best to manage them contributes towards the achievement of this vision from the perspective of SECI Model. It had been emphasized by the model that strengthening of their human resource management and knowledge management functions are crucial for the continuous success of the Multimedia Super Corridor status companies in particular and the nation in general.